The Effect of Self-efficacy and Goal Orientation toward Accountant's Work Performance - Johanes, Johanes (Jurnal KIAFE, 2020)
This study aims to provide empirical research related to explain the indicator of personality traits that consisted of self-efficacy and goal orientation toward accountant"™s work performance and accountant"™s outcome. This research study discuss about self-efficacy and goal orientation toward accountant"™s work performance, using variables: self-efficacy, goal orientation, and work performance. This study focuses on accountants that work in Pontianak area at public accountant office or private business company. Data used are primary data that collected by survey questionnaires. Data are taken by using criteria (Convenience Sampling method). Data are analyzed by using multiple linear regression analysis and hypothesis test that consisted of Coefficient of Determinants (R2), F-Test and T-Test (Partial) to find the relation of self-efficacy, goal orientation toward accountant"™s work performance.The research"™s result show self-efficacy has positive and strong relation to accountant"™s work performance, where individuals who are high in self-efficacy will produce a better job outcome and they tend to be more confidence in doing the tasks. Meanwhile for goal orientation that divided into three items which are, learning goal orientation, performance-approach goal orientation, performance-avoidance goal orientation have no relationship with accountant"™s work performance. This condition might be caused by the low understanding of accountant to implement and conduct this kind of personality trait in their work place. Keywords: self-efficacy, goal orientation, work performanceAkhtar, N. (2008). On Privileging the Role of Gaze in Infant Social Cognition. Research Journal. Alessandri, G., Borgogni, L., Schaufeli, W., Caprara, G., & Consiglio, C. (2015). From Positive Orientation to Job Performance: The Role of Work Engagement and Self-efficacy Beliefs. Journal of Happiness Studies, 767-788. As'ad, M. (1998). Psikologi Industri. Yogyakarta: Liberty. Bandura, A. (1977). Self-efficacy: toward a unifying theory of behavioral change. Psychological Review, 191-215. Bandura, A. (1982). Self-efficacy: mechanism in human agency. American Psychologist, 122-47. Bandura, A. (1999). Social cognitive theory of personality. Handbook of Personality: Theory and Reserach, 154-196. Bandura, A. (2001). Social cognitive theory: an agentic perspective. Annual Review of Psychology, 1-26. Baron, R. A., & Byrne, D. E. (2004). Social Psychology: With Research Navigator. Pearson. Bono, J., & Judge, T. (2003). Core selfevaluations: a review of the trait and its role in job satisfaction and job performance. European Journal of Personality, S5-S18. Carmeli, A., Gilat, G., & Waldman, A. D. (2007). The role of perceived organizational performance in organizational identification, adjustment and job performance. Journal of Management Studies, 972-992. Cetin, F., & Askun, D. (2018). The effect of occupational selfefficacy on work performance through intrinsic motivation. Management Reserach Review. Crothers, L., Hughes, T., & Morine, K. (2008). Theory and cases in school-based consultation: A resource for school psychologists, school conselor, special educators, and other mental health professionals. Research Journal. Deci, E., & Ryan, R. (1985). Intrinsic Motivation and SelfDetermination in Human Behavior. NY: Springer Science & Business. Ford, C. (1996). A theory of individual creative action in multiple social domains. Academy of Management Review. Gani, I. (2015). Alat Analisis Data: Aplikasi Statistik untuk Penelitian Bidang Ekonomi dan Sosial. Andi. Ghozali, I. (2007). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Undip. Ghozali, I. (2011). Aplikasi Analisis Multivariate Dengan Program SPSS. Semarang. Gist, M., & Mitchell, T. (1992). Selfefficacy: a theoritical analyssi of its determinants and malleability. Academy of Management Review, 183-211. Hox, J. (2002). Multilevel Analysis. Techniques and Applications. NJ: Erlbaum Mahwah. Judge, T., Locke, E., & Durham, C. (1997). The dispositional causes of job satisfaction: a core evaluations approach. Research in Organizational Behavior, 151-188. Locke, E., & Latham, G. (1990). A Theory of Goal Setting and Task Performance. A Theory of Goal Setting and Task Performance. Mangos, P. M., & Steele-Johnson, D. (2001). The role of subjective task complexity in goal orientation, self-efficacy, and performance relation. Human Performance, 169-185. Miao, C., Qian, S., & Ma, D. (2017). The Relationship between entrepreneurial self-efficacy and firm performance: a metaanalysis of main and moderator effects. Journal of Small Business Management, 245-265. Nevid, J. (2009). Psychology: Concepts and applications. Reserach Journal. Priyatno, D. (2010). Teknik Mudah dan Cepat Melakukan Analisis Data Penelitian dengan SPSS. Gava Media. Raudenbush, S., Bryk, T., & Congdon, R. (2010). HLM 7.01: Hierarchical Linear and Nonlinear Modeling [Computer Software]. Chicago: Scientific Software International. Redmond, B. (2010). Self-efficacy theory: Do I think that I can succeed iin my work? Work Attitudes and Motivation. Rigotti, T., Schyns, B., & Mohr, G. (2018). A short version of the occupational self-efficacy scale: structural and construct validity across five countries. Journal of Career Assestment, 238-255. Santoso, S. (2010). Statistik Multivariat. Jakarta: PT. Elex Media Komputindo. Sanusi, Z. M., Iskandar, T. M., Monroe, G. S., & Saleh, N. M. (2018). Effects of goal orientation, selfefficacy and task complexity on the audit judgement performance of Malaysian auditor. Accounting, Auditing & Accountability Journal, 75-95. Sarwono, J., & Suhayati, E. (2010). Riset Akuntansi Menggunakan SPSS. Yogyakarta: Graha Ilmu. Schuler, R. S., & Jackson, S. E. (2005). A Quarter-Centery Review of Human Reseource Management in the U.S.: The Growth in Importance of the International Perspective. Management Revue. Shih, K.-H., Hsieh, Y. R., & Lin, B. (2009). Moderator effects to internal audits' self-efficacy and job involvement. International Journal of Accounting & Information Management, 151- 165. Simamora, B. (2005). Analisis Multivariat Pemasaran. Jakarta: Gramedia Pustaka Utama. Sinambela, L. P. (2012). Kinerja Pegawai. Yogyakarta: Graha Ilmu. Siregar, S. (2010). Statistika Deskriptif Untuk Penelitian: Dilengkapi Perhitungan Manual dan Aplikasi SPSS Versi 17. Rajawali Pers. Stajkovic, A., & Luthans, F. (1998). Self-efficacy and work-related performance: a meta-analysis. Psychological Bulletin, 240. Sudarmanto, R. G. (2005). Analisi Regresi Linear Ganda dengan SPSS. Yogyakarta: Graha Ilmu. Sugiyono. (1999). Metode Penelitian Bisnis. Bandung: Alfabeta. Sugiyono. (2004). Metodel Penelitian Administrasi. Bandung: Alfabeta. Umar, H. (2000). Research Method in Finance and Banking. Jakarta: Gramedia Pustaka Utama. Umar, H. (2003). Metode Riset Perilaku Organisasi. Jakarta: Gramedia Pustaka Utama. VandeWalle, D. (2001). Why wanting to look successful doesn't always lead to success. Organizational Dynamics, 162-171. Wood, R., & Bandura, A. (1989). Social cognitive theory of organizational management. Academy of Management Review, 361-384. Wood, R., Bandura, A., & Bailey, T. (1990). Mechanisms governing organizational performance in complex decision-making environments. Organizational Behavior and Human Decision Processes, 181-201.